Saving the animals of Ukraine [videorecording (DVD)] - Filatov, Yevhen (PBS, 2024)
"Amid violence and war, Ukrainian citizens are coming together to rescue animals that have been left behind by those forced to flee. From cats and dogs in abandoned buildings to lions and tigers in the nation's zoos, extraordinary rescue efforts are underway to bring them to safety. The film is a tribute to the very best of the human spirit despite the horrors of war. Directed by Ukrainian YouTuber Anton Ptushkin"--Container.